Optimalisasi Bank Sampah Melalui Penataan Fasilitas Dan Edukasi Lingkungan Di RW 045 Sumberjaya - Syafiqoh Syaqurani; Dinar Soelistyowati; Inna Anjal Oktasari; Vamdro Sahala Tota Marpaung; Muhammad Quentin Ilham; Muhammad Keylan Aullia; Danu Ramaditya; Alfath Audriansyah; Annisa Rizky Ananda; Arya Bintang Adi Saputra; Hudzaifah Hakim; Putri Shabira Bilqist; Nazeline Angelita Syalsabila; Syeva Geysca Khalisha Kandow; Muhammad Sabila Zidane (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2026)
Waste management in residential areas remains a significant challenge that requires active community participation through the strengthening of community-based waste management. This community service program aimed to optimize the management of the Waste Bank in RW 045, Villa Bekasi Indah 2, Sumberjaya Village, South Tambun District, Bekasi Regency by strengthening administrative management, improving waste bank facilities, and providing environmental education media. The implementation method consisted of several stages, including observation and problem identification, coordination with local community leaders and waste bank managers, implementation of activities through waste bank administrative data recapitulation, improvement and decoration of the waste bank area, and the development and installation of waste decomposition information boards as environmental education media. The program concluded with monitoring and evaluation to assess its effectiveness. The results showed that the waste bank administration became more organized, the waste bank area became cleaner and more attractive, and the environmental education media improved community understanding of waste segregation and proper waste management. Furthermore, the program encouraged greater community participation in community-based waste management and is expected to contribute to the development of a cleaner, healthier, and more sustainable environment.